Structural Parameters Optimization of Corona Ring of Tethered Balloon-Type VLF Antenna - Ao Wang; Xianqiang Li; Huajun Zhang; Ji Tian; Wenchuang Zhou (International Journal of Antennas and Propagation)
The antenna end of the tethered balloon-type high-power VLF communication system will be exposed to an extremely strong alternating electric field environment when it is in operation. Due to dielectric loss, an abnormal temperature rise may occur at the antenna end, which may lead to an antenna fracture in serious cases. It is an effective measure to install a corona ring at the end of the antenna to prevent such accidents. In this paper, the structural parameters of the corona ring, including ring radius, tube radius, and ring depth, are optimized based on intelligent optimization algorithm to significantly improve the electric field distribution and restrain the temperature rise to the maximum extent. The effectiveness of the optimization results is verified by simulation.